Controllable Enhancement of Evanescent and Transmitted Waves by a Plasma Sphere - Shi, Wenxuan; Yuan, Bin; Mao, Junfa (Frontiers in Physics, 2022)
In this study, we present that the plasma sphere can focus and enhance the evanescent and transmitted waves. Electromagnetic waves propagating in a plasma sphere with a positive or negative permittivity, which leads to the enhancement of transmitted and evanescent waves, are analyzed. The intensity of the focused beam can be hundreds of times stronger than that of the incident wave. The enhancement effect is associated with plasma frequency, collision frequency, and incident wave frequency. The results illustrate that the electromagnetic wave can be focused, reflected, and oscillated by controlling the electromagnetic parameters of the plasma sphere. With a strong field enhancement available, it is possible to be used in microwave power amplifiers, plasma antennas, reflectors, etc.